2014
DOI: 10.4236/ajps.2014.53046
|View full text |Cite
|
Sign up to set email alerts
|

The Length and Density of Prickles on <i>Zanthoxylum ailanthoides</i> (Rutaceae): A Comparison of Japanese Islands with Different Sika Deer Browsing Pressures

Abstract: To determine the effects of sika deer (Cervus nippon) browsing on the physical defences of the Japanese pricklyash "Zanthoxylum ailanthoides Sieb. et Zucc." (Rutaceae), we compared the length and density of prickles on Japanese islands which were under different browsing pressures. We measured the length and density of prickles on the midribs, leaf rachis, and stems. We found that the prickles of Z. ailanthoides on Kashima island were not significantly longer or at higher densities than those in the neighbouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In Kinkazan Island, Takatsuki (2006) reported the similar situation to those of Kashima Island. In contrast to these species, Zanthoxylum ailanthoides has relatively long leaf and stem prickles, and prickle length and density in this species is not significantly different between Kashima Island and the mainland, but is increased on Akune Island (Takei et al, 2014), suggesting that Z. ailanthoides may be able to resist heavy browsing. The results of the present study, and the results of previous studies by Takei et al (2013;2014), suggest that Z. ailanthoides can grow in areas where browsing pressure by sika deer is relatively high, whereas R. croceacanthus and R. sieboldii can not do it.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…In Kinkazan Island, Takatsuki (2006) reported the similar situation to those of Kashima Island. In contrast to these species, Zanthoxylum ailanthoides has relatively long leaf and stem prickles, and prickle length and density in this species is not significantly different between Kashima Island and the mainland, but is increased on Akune Island (Takei et al, 2014), suggesting that Z. ailanthoides may be able to resist heavy browsing. The results of the present study, and the results of previous studies by Takei et al (2013;2014), suggest that Z. ailanthoides can grow in areas where browsing pressure by sika deer is relatively high, whereas R. croceacanthus and R. sieboldii can not do it.…”
Section: Resultsmentioning
confidence: 66%
“…Takei et al (2013) found that the prickles of Rubus sieboldii Blume (Rosaceae) on Kashima were significantly longer and at a higher density than those from ungrazed areas of the mainland ( Figure 1B). Although this result suggests that plant species with prickles have increased their physical defences against browsing, the prickles of Zanthoxylum ailanthoides are not significantly different from those on plants on the mainland (Takei et al, 2014). Consequently, Takei et al (2014) suggested that the difference in the high numbers of prickles between R. sieboldii and Z. ailanthoides was based on the level of browsing pressure on Kashima Island.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Zanthoxylum ailanthoides display long prickles to protect from sika deer browsing, suggesting that the increase in prickle length and density is an adaptive defense strategy (Takei et al, 2014a(Takei et al, , 2014b.…”
Section: Degs Enrichment Analysismentioning
confidence: 99%
“…[4], R. vestitus Weihe et Nees [5] [6] and Aralia spinosa L. [7], the increased length and number of Zanthoxylum ailanthoides Siebold et Zucc. [8], and the increased trichome density in Urtica thunbergiana Sieb. et Zucc.…”
Section: Introductionmentioning
confidence: 96%